2007
DOI: 10.3354/meps332011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of functional biodiversity and species-specific traits of benthic fauna for ecosystem functions in marine sediment

Abstract: Fauna have been found to regulate important biogeochemical properties and ecosystem functions in benthic environments. In this study, we focused on how functional biodiversity and species-specific traits of benthic macrofauna affect key ecosystem functions related to organic matter mineralization and cycling of nutrients in surface sediments. Dominant benthic invertebrates from the Baltic Sea and the Skagerrak were classified into functional groups in accordance with their behaviour, feeding and sediment rewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(119 citation statements)
references
References 44 publications
(43 reference statements)
2
115
0
2
Order By: Relevance
“…Those authors concluded that ecosystems with higher species diversity (maximum number of species = 3) incorporated more carbon and nitrogen, displayed more efficient trophic transfer of phytodetritus and were more productive than monocultures. The importance of single species and species-specific traits on ecosystem functioning has also been demonstrated (Solan et al 2004, Norling et al 2007, Godbold et al 2009b). Hence, we now focus on Linopherus sp.…”
Section: Effect Of Linopherus Sp Nov On Ecosystem Responses To Gradmentioning
confidence: 99%
“…Those authors concluded that ecosystems with higher species diversity (maximum number of species = 3) incorporated more carbon and nitrogen, displayed more efficient trophic transfer of phytodetritus and were more productive than monocultures. The importance of single species and species-specific traits on ecosystem functioning has also been demonstrated (Solan et al 2004, Norling et al 2007, Godbold et al 2009b). Hence, we now focus on Linopherus sp.…”
Section: Effect Of Linopherus Sp Nov On Ecosystem Responses To Gradmentioning
confidence: 99%
“…However, the extent to which one can assume that morphologically and taxonomically similar species have similar functional roles is not well understood (Chalcraft & Resetarits 2003, Bjelke & Herrmann 2005, and studies investigating differences in functional roles within closely related taxa are limited (for marine exceptions see Bellwood & Choat 1990, Purcell & Bellwood 1993, Duffy et al 2001, Choat et al 2002, Norling et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Marine nutrient cycling occurs when organic matter in the water column falls to the seafloor and is degraded by microbes, infauna, and epifauna such that nutrients are released back into the water column via bioturbation and predation (Norling et al 2007). The rate of nutrient cycling depends not only on depth, ocean currents, and seafloor properties but also on the associated biological communities (Biles et al 2002).…”
Section: Discussionmentioning
confidence: 99%